Difficulties in land regulation in Greater Lomé and Atakpamé. Contexts and explanatory factors - Adjayi, Komi Arsène Fulbert; Kpotchou, Koffi; NASSI, Karl Martial; Atchon, Kodjo Sena; Gbekley, Efui Holaly (Edelweiss Applied Science and Technology, 2024)
In Togo and particularly in greater Lomé and Atakpamé, we see that the State has difficulty regulating or controlling land. The objective of this article is to examine the factors that make land regulation difficult in Togo in general and in greater Lomé and Atakpamé in particular. To achieve this, the research used quantitative and qualitative approaches based respectively on questionnaire administration and individual interview techniques. For the quantitative survey, 208 landowners were interviewed in greater Lomé compared to 122 in Atakpamé. Concerning the qualitative approach, 24 resource people were interviewed in greater Lomé compared to 21 in Atakpamé. The results of the investigations showed that the non-registration of plots purchased in the cadastral service, the absence of land mapping, unconventional subdivisions, land speculation and the purchase of family land constitute factors which make regulation and management difficult. land security. To compensate for illegal urban practices and sustainably control land, it is necessary, in addition to existing measures, to adopt an inclusive and participatory approach which would bring populations, local elected officials and the state into a chain of collaboration.